PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), STRUKTUR KEPEMILIKAN, MANAJEMEN LABA, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Noviyanti, Fanny Richa; Anggra, Eva; Muttaqin, Ibnu (PERMANA, 2017)
The purpose of this research is to analyze the effect of corporate social responsibility disclosure, ownership structure, earnings management, and leverage toward tax agressiveness. The population in this research are all companies listed on BEI with coal minning company as a sampel. Using purposive sampling as the sampling technique, 6 companies are selected as samples. The reasearch period used is 5 years period. Data analysis technique used in this research is multiple linear regression, which previously performed the descriptive statistics, the classic assumption test, and hypothesis testing. The results of this research in the first hypothesis shows that corporate social responsibility disclosure, ownership structure, earnings management, and leverage have no effect simultaneously toward tax agressiveness with significance level of 0,482. The second hypothesis showed the corporate social responsibility disclosure has no significant effect toward tax agressiveness on the level of 0,453. The third showed the ownership structure has no significant effect toward tax agressiveness on the level of 0.182. The fourth hypothesis showed that earnings management has no significant effect toward tax agressiveness on the level of 0.946, and the fifth hypothesis show leverage has no significant effect toward tax agressiveness on the level of 0,295. Keywords: corporate social responsibility (CSR), ownership structure, earnings management, leverage, tax aggressiveness